Philosophy made slightly less difficult a beginner's guide to life's big questions - DeWeese, Garrett J., 1947-; Moreland, James Porter, 1948- (Downers Grove, Ill. : InterVarsity Press, 2005)
Garrett DeWeese and J.P. Moreland understand this frustration and in this book offer help to make philosophy at least slightly less difficult. In straightforward language with everyday examples, they explain the basics needed to understand philosophical concepts and thus bring clarity to discussions of life's big questions.
Where do I start -- What is real? Metaphysics -- How do I know? Epistemology -- How should I live? Ethics -- What am I? Philosophical and theological anthropology -- How should Christians think about science? Philosophy of science -- Where do I go from here? Worldview struggle and intellectual crisis.
Includes bibliographical references (p. [161]-163) and indexes.
Description based on print version record.
Keywords: Philosophy; PHILOSOPHY / Essays; PHILOSOPHY / Reference; Electronic books